(Dys)regulation of Protein Metabolism in Skeletal Muscle of Humans With Obesity - Freitas, Eduardo D. S.; Katsanos, Christos S. (Frontiers in Physiology, 2022)
Studies investigating the proteome of skeletal muscle present clear evidence that protein metabolism is altered in muscle of humans with obesity. Moreover, muscle quality (i.e., strength per unit of muscle mass) appears lower in humans with obesity. However, relevant evidence to date describing the protein turnover, a process that determines content and quality of protein, in muscle of humans with obesity is quite inconsistent. This is due, at least in part, to heterogeneity of protein turnover in skeletal muscle of humans with obesity. Although not always evident at the mixed-muscle protein level, the rate of synthesis is generally lower in myofibrillar and mitochondrial proteins in muscle of humans with obesity. Moreover, alterations in the synthesis of protein in muscle of humans with obesity are manifested more readily under conditions that stimulate protein synthesis in muscle, including the fed state, increased plasma amino acid availability to muscle, and exercise. Current evidence supports various biological mechanisms explaining impairments in protein synthesis in muscle of humans with obesity, but this evidence is rather limited and needs to be reproduced under more defined experimental conditions. Expanding our current knowledge with direct measurements of protein breakdown in muscle, and more importantly of protein turnover on a protein by protein basis, will enhance our understanding of how obesity modifies the proteome (content and quality) in muscle of humans with obesity.